Kepuasan Masyarakat Terhadap Pelayanan Rumah Sakit Rujukan di Provinsi Kepulauan Riau Tahun 2019: Community Satisfaction with Referral Hospital Services in Riau Islands Province Riau Year 2019 - Kiki Rizki Dasaryandi; Yulastri Arif; Eka Roza Wijaya (Fakultas Keperawatan Universitas Andalas, 2019)
Patient satisfaction is one indicator of the quality of health services. However, it needs to be recognized that patient expectations have not been fulfilled by health services, this is reflected in the still low level of patient satisfaction in various health service centers. The purpose of this study was to analyze and compare patient satisfaction in three government hospitals in Batam City. The government hospitals are Rumah Sakit Umum Pusat (RSUP), Rumah Sakit Umum Daerah (RSUD), and RSBP. This research is a quantitative research with descriptive analytic design and cross sectional approach. The study population was patients who visited all three hospitals with a total sample of 762 people taken by accidental sampling technique. The data was taken using a questionnaire issued by the Ministry of Defense of the Republic of Indonesia regarding the Community Satisfaction Index (IKM) on hospital services. This research was conducted for 3 months starting from April to June 2019. The dependent variable of the study was Patient Satisfaction measured using SMIs and the independent variable was service performance in three Riau Islands referral hospitals. The results showed that the RSUD and RSUP had a good service performance assessment, while the RSBP service performance was judged to be poor. However, the satisfaction of patients assessed through IKM in RSBP is the highest compared to the other two hospitals. This study shows the low performance value of RSBP services is not in line with the high IKM value. This can be caused even though they do not have good service performance, but because RSBP is the last reference, which makes them have no choice but to be satisfied with the existing conditions. Nevertheless, it is hoped that hospitals can improve the performance of service providers so that they can satisfy patients as service users.